Sosialisasi dan Pelatihan Aplikasi Teknologi Building Information Building (BIM) Pada Dinas Pekerjaan Umum dan Penataan Ruang (PUPR) Kabupaten Gowa - Fakhruddin Fakhruddin (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2021)
Building Information Modeling (BIM) is a digital representation of a building's physical and functional characteristics. BIM contains all information about building elements that is used as a basis for decision making throughout the building's life cycle, from concept to demolition. Tekla Structures is a BIM-supporting software that allows you to create and manage data accurately and in detail, as well as create 3D structural models without forgetting complex materials and structures. The Indonesian government has issued a number of regulations concerning the implementation of BIM in the construction industry. The next challenge is figuring out how to introduce this BIM application technology and encourage all relevant construction sector stakeholders to use it. As a result, the goal of this community service activity is to provide an introduction to Building Information Modeling as well as basic skills in the use of BIM technology applications using Tekla Structures software. This activity was held in Gowa Regency and was attended by 25 participants who were employees of the Gowa Regency Public Works and Spatial Planning Office, as well as representatives of consultants and contractors. Training activities include a general introduction to BIM (BIM Overview), registration of Tekla Campus, the introduction of Tekla Campus features (Tekla Interface and Starting), Tekla Fundamental Training, and examples of more complex cases.